The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

The specificity of Burkholderia symbionts in the social amoeba farming symbiosis: Prevalence, species, genetic and phenotypic diversity - Tamara S. Haselkorn; Susanne DiSalvo; Jacob W. Miller; Usman Bashir; Debra A. Brock; David C. Queller; Joan E. Strassmann (Molecular Ecology, 2019)
The establishment of symbioses between eukaryotic hosts and bacterial symbionts in nature is a dynamic process. The formation of such relationships depends on the life history of both partners. Bacterial symbionts of amoebae may have unique evolutionary trajectories to the symbiont lifestyle, because bacteria are typically ingested as prey. To persist after ingestion, bacteria must first survive phagocytosis. In the social amoeba Dictyostelium discoideum , certain strains of Burkholderia bacteria are able to resist amoebal digestion and maintain a persistent relationship that includes carriage throughout the amoeba's social cycle that culminates in spore formation. Some Burkholderia strains allow their host to carry other bacteria, as food. This carried food is released in new environments in a trait called farming. To better understand the diversity and prevalence of Burkholderia symbionts and the traits they impart to their amoebae hosts, we first screened 700 natural isolates of D. discoideum and found 25% infected with Burkholderia . We next used a multilocus phylogenetic analysis and identified two independent transitions by Burkholderia to the symbiotic lifestyle. Finally, we tested the ability of 38 strains of Burkholderia from D. discoideum , as well as strains isolated from other sources, for traits relevant to symbiosis in D. discoideum . Only D. discoideum native isolates belonging to the Burkholderia agricolaris , B. hayleyella , and B. bonniea species were able to form persistent symbiotic associations with D. discoideum. The Burkholderia – Dictyostelium relationship provides a promising arena for further studies of the pathway to symbiosis in a unique system.

Nancy A. Moran ‐ Recipient of the 2017 Molecular Ecology Prize - David C. Queller (Molecular Ecology, 2018)

Which phenotypic traits of Dictyostelium discoideum farmers are conferred by their bacterial symbionts? - Debra A. Brock; Kai Jones; David C. Queller; Joan E. Strassmann (Symbiosis, 2016)

Mind the gap: a comparative study of migratory behavior in social amoebae - Owen M. Gilbert; Jennie J. Kuzdzal-Fick; David C. Queller; Joan E. Strassmann (Behavioral Ecology and Sociobiology, 2012)

Discovery of a large clonal patch of a social amoeba: implications for social evolution - OWEN M GILBERT; DAVID C QUELLER; JOAN E STRASSMANN (Molecular Ecology, 2009)
Studies of genetic population structures of clonally reproducing macro‐organisms have revealed large areas where only one clone is found. These areas, referred to as clonal patches, have not been shown to occur in free‐living microbes until now. In free‐living microbes, high genetic diversity at local scales is usually maintained by high rates of dispersal. We report, however, a highly dense, 12‐m clonal patch of the social amoeba Dictyostelium discoideum in a cattle pasture located in a Texas Gulf Coast prairie. We confirm the presence of only one clone by the analysis of 65 samples and amplification of 10 polymorphic microsatellite loci. Samplings of additional cattle pastures nearby showed higher clonal diversity, but with a density of D. discoideum isolates lower than in the clonal patch. These findings show that high rates of microbial dispersal do not always produce genetic diversity at local scales, contrary to the findings of previous studies. The existence of clonal patches may be particularly important for microbial social evolution.

Male production in stingless bees: variable outcomes of queen–worker conflict - Eva Tóth; Joan E. Strassmann; Paulo Nogueira‐Neto; Vera L. Imperatriz‐Fonseca; David C. Queller (Molecular Ecology, 2002)
The genetic structure of social insect colonies is predicted to affect the balance between cooperation and conflict. Stingless bees are of special interest in this respect because they are singly mated relatives of the multiply mated honeybees. Multiple mating is predicted to lead to workers policing each others’ male production with the result that virtually all males are produced by the queen, and this prediction is borne out in honey bees. Single mating by the queen, as in stingless bees, causes workers to be more related to each others’ sons than to the queen's sons, so they should not police each other. We used microsatellite markers to confirm single mating in eight species of stingless bees and then tested the prediction that workers would produce males. Using a likelihood method, we found some worker male production in six of the eight species, although queens produced some males in all of them. Thus the predicted contrast with honeybees is observed, but not perfectly, perhaps because workers either lack complete control or because of costs of conflict. The data are consistent with the view that there is ongoing conflict over male production. Our method of estimating worker male production appears to be more accurate than exclusion, which sometimes underestimates the proportion of males that are worker produced.

Polymorphic microsatellite loci for primitively eusocial Stenogastrine wasps - Yong Zhu; Monica Landi; David C. Queller; Stefano Turillazzi; Joan E. Strassmann (Molecular Ecology, 2000)

Polymorphic microsatellite loci for primitively eusocial Stenogastrine wasps - Yong Zhu; Monica Landi; David C. Queller; Stefano Turillazzi; Joan E. Strassmann (Molecular Ecology, 2000)

The genetic structure of swarms and the timing of their production in the queen cycles of neotropical wasps - JOAN E. STRASSMANN; KEITH F. GOODNIGHT; CEAL J. KLINGLER; DAVID C. QUELLER (Molecular Ecology, 1998)
Kin selection theory has received some of its strongest support from analyses of within‐colony conflicts between workers and queens in social insects. One of these conflicts involves the timing of queen production. In neotropical wasps, new queens are only produced by colonies with just one queen while males are produced by colonies with more queens, a pattern favoured by worker interests. We now show that new colonies, or swarms, have few queens and variable within‐colony relatednesses which means that their production is not tied to new queen production. The queens in these swarms are seldom the mothers of the workers in the swarm. Therefore, either colonies producing swarms have very many queens, or queens joining daughter swarms are reproductive losers on the original colonies. As new colony production is not linked to queen production, it can occur at the ecologically optimum time, i.e. the rainy season. This disassociation between queen production and new colony production allows worker interests in sex ratios to prevail without hampering new colony production at the most favourable season, an uncoupling that may contribute to the ecological success of the Epiponini.

Trinucleotide Microsatellite Loci and Increased Heterozygosity in Cross-Species Applications in the Social Wasp, Polistes - Joan E. Strassmann; John M. Peters; Karen Barefield; Carlos R. Solís; Colin R. Hughes; David C. Queller (Biochemical Genetics, 1997)

Colony life history and demography of a swarm-founding social wasp - J. E. Strassmann; Carlos R. Solís; C. R. Hughes; Keith F. Goodnight; David C. Queller (Behavioral Ecology and Sociobiology, 1997)

Control of reproduction in social insect colonies: individual and collective relatedness preferences in the paper wasp, Polistes annularis - David C. Queller; J. M. Peters; Carlos R. Solís; Joan E. Strassmann (Behavioral Ecology and Sociobiology, 1997)

Microsatellite variation in a social insect - Madhusudan Choudhary; Joan E. Strassmann; Carlos R. Solís; David C. Queller (Biochemical Genetics, 1993)

Microsatellite variation in a social insect - Madhusudan Choudhary; Joan E. Strassmann; Carlos R. Solís; David C. Queller (Biochemical Genetics, 1993)